Total baseline tumor size predicts survival among patients with advanced small-cell lung cancer receiving chemotherapy plus programmed death-ligand 1 inhibitor as first-line therapy: a multicenter retrospective observational study - Tanaka, Anna; Teranishi, Shuhei; Kajita, Yukihito; Hirose, Tomofumi; Kaneko, Ayami; Sairenji, Yu; Kawashima, Hidetoshi; Yumoto, Kentaro; Tsukahara, Toshinori; Miura, Kenji; Kobayashi, Nobuaki; Yamamoto, Masaki; et al. (Frontiers in Oncology, 2024)
IntroductionTotal baseline tumor size (BTS) is a prognostic factor for programmed death 1 and programmed death-ligand 1 (PD-L1) inhibitor treatments. However, the prognostic value of total BTS for patients with small-cell lung cancer (SCLC) who receive chemotherapy plus PD-L1 inhibitor remains unknown. Thus, in this study, we aimed to determine whether total BTS is associated with prognosis in patients with SCLC who receive chemotherapy plus PD-L1 inhibitor as first-line therapy.MethodsThis study included patients with extensive-stage SCLC or post-chemoradiotherapy recurrence of limited-stage SCLC who received chemotherapy plus PD-L1 inhibitor as first-line therapy from August 2019 to December 2022. The two lesions with the largest diameter among the measurable lesions in each organ were selected from up to five organs (maximum of 10 lesions), and the sum of all diameters was defined as total BTS. The patients were divided into two groups, large or small, with total BTS using X-tile software. Median survival was analyzed using the Kaplan–Meier method, and the groups were compared using the log-rank test. Univariate and multivariate analyses examined the association between total BTS and prognosis.ResultsFifty patients were included; 14% had large total BTS (>183.2 mm) and 86% had small total BTS (≤183.2 mm). The median observation period was 10.5 months. The large total BTS group showed significantly worse overall survival than the small total BTS group (median: 26.8 months vs. 5.7 months, P = 0.0003). The multivariate analysis indicated that large total BTS was an independent negative predictor of overall survival (hazard ratio: 7.14, 95% confidence interval: 1.89–26.96).DiscussionTotal BTS is a potentially useful prognostic factor for patients with advanced SCLC who receive chemotherapy plus PD-L1 inhibitor as first-line therapy.